Interference of corn yield corrections methods on adaptability and stability parameters - Cargnelutti Filho, Alberto (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The objective of this work was to verify the interference of corn yield corrections methods, considering plants population, on the adaptability and stability parameters of corn cultivars, estimated by Lin & Binns method modified by Carneiro. The adjustment, or not, of corn cultivars grain yield, in 31 corn trials, was made with the methods: without correction, three rule, Zuber method, covariance of the average population, covariance of the ideal population, method proposed by Cruz, method proposed by Vencovsky & Cruz, and the method of stratified correction. The magnitude of correction influence of each method used Spearman rank correlation, in relation to the data without correction. The correction methods provide parameters to cultivars, to different levels of agreement, in the adaptability and stability in relation to data without correction. Methods of correction for covariance analysis of average and ideal populations, proposed by Vencovsky & Cruz, and method of the stratified correction cause greater agreement on adaptability and stability parameters to cultivars, in relation to data without correction.